The Analysis of the Characterization of the Pevensies in the Novel of Narnia: The Lion, the Witch, and the Wardrobe - Made Vera Yanti (STKIP PGRI Lubuklinggau, 2021)
The writing of Clive Staples Lewis, especially his novel titled Narnia: The Lion, the Witch, and the Wardrobe had interesting characters. The characterization of the Pevensies strongly influenced the storyline of the novel. Therefore, the aim of this study was describing the characterization of the Pevensies in the novel The Chronicles of Narnia: the Lion, the Witch, and the Wardrobe. This research was a qualitative research with non-instrument. The research found that the characteristics of the Pevensies were different from another. This study was expected to give meaningful information for the reader about the characterization of the Pevensies in the Lewis’s writing.